Microcystin-Induced Immunotoxicity in Fishes: A Scoping Review - Wang Lin (MDPI AG, 2021)
Cyanobacteria (blue-green algae) have been present on Earth for over 2 billion years, and can produce a variety of bioactive molecules, such as cyanotoxins. Microcystins (MCs), the most frequently detected cyanotoxins, pose a threat to the aquatic environment and to human health. The classic toxic mechanism of MCs is the inhibition of the protein phosphatases 1 and 2A (PP1 and PP2A). Immunity is known as one of the most important physiological functions in the neuroendocrine-immune network to prevent infections and maintain internal homoeostasis in fish. The present review aimed to summarize existing papers, elaborate on the MC-induced immunotoxicity in fish, and put forward some suggestions for future research. The immunomodulatory effects of MCs in fish depend on the exposure concentrations, doses, time, and routes of exposure. Previous field and laboratory studies provided strong evidence of the associations between MC-induced immunotoxicity and fish death. In our review, we summarized that the immunotoxicity of MCs is primarily characterized by the inhibition of PP1 and PP2A, oxidative stress, immune cell damage, and inflammation, as well as apoptosis. The advances in fish immunoreaction upon encountering MCs will benefit the monitoring and prediction of fish health, helping to achieve an ecotoxicological goal and to ensure the sustainability of species. Future studies concerning MC-induced immunotoxicity should focus on adaptive immunity, the hormesis phenomenon and the synergistic effects of aquatic microbial pathogens.